Metode Pembelajaran Bahasa Secara Jarak Jauh untuk Peserta Didik Gangguan Komunikasi di Sekolah Dasar di Era Pandemi Covid-19 - Tanjungsari Sekaringtyas (Jurnal Penelitian Pendidikan Khusus, 2022)
This research is a research that uses qualitative research methods. The background of the research found problems in the learning system in schools from face-to-face learning to distance learning due to the covid-19 pandemic, both regular schools and special schools (SLB). This study aims to describe how the planning, implementation, supporting factors and inhibiting factors for the implementation of distance learning for children with communication disorders at SDS Lab Setiabudi Jakarta. The research hypotheses are: 1) Planning by compiling programs includes essential materials and teacher's ability to use technology, 2) Implementation using online and offline methods with strategies utilizing technology, 3) Supporting factors include collaboration between the school and parents, assistance from the school and free quota assistance from the government, 4) The inhibiting factors for the implementation of distance learning are parents who have permanent jobs, parents who do not understand the task, and where students live who have difficulty accessing the internet network.